Narrative flexibility in brief psychotherapy for depression. (2nd November 2017) - Boritz, Tali; Barnhart, Ryan; Angus, Lynne; Constantino, Michael J.
Abstract: Objective: This study aimed to further understand how narrative flexibility contributes to therapeutic outcome in brief psychotherapy for depression utilizing the Narrative-Emotion Process Coding System (NEPCS), an observational measure that identifies specific markers of narrative and emotion integration in therapy sessions. Method: The present study investigated narrative flexibility by examining the contribution of NEPCS shifting (i.e., movement between NEPCS markers) in early, middle, and late sessions of client-centred therapy (CCT), emotion-focused therapy (EFT), and cognitive therapy (CT) and treatment outcome (recovered versus unchanged at the therapy termination). A logistic regression, with Wald tests of parameter estimates and pairwise comparisons, was used to test the study hypotheses. Results: Results demonstrated that for recovered clients, the probability of shifting over the course of a therapy session was constant, whereas the probability of shifting declined for unchanged clients as the session progressed. There was also evidence that longer duration of time spent in any single NEPCS marker was negatively associated with shifting for both recovered and unchanged clients, although the effect was stronger for unchanged clients. Conclusions: The results provided preliminary support for the contribution of narrative flexibility to treatment outcomes in EFT, CCT, and CT treatments of depression.